The Effect of Rural Guide Plan on Objective Quality of Life among Rural Communities in Fariman County - Aliakbar Anabestani; Hamdollah Sojasi Qeidari; Fahime Jafari (تحقیقات کاربردی علوم جغرافیایی)
The rural guide plan is the most important tool in the management of rural development in Iran. The final purpose of the plan, improvement of life quality and providing a safe and attractive environment to live in rural areas. The aim of this study is to emphasize the characteristics rural guide plans, which include: Improve the quality of housing, street network, land use and access to services, environmental rural its effects on the objective quality of life of the villagers tested. The research method in present study was functional in terms of purpose, and analytical-descriptive and solidarity methodologically. The study population was selected from 22 villages in which guide plan had been implemented, among them 8 villages with a population of 3835 households was selected by using sampling method. From the selected villages by using sampling method (Cochran), 249 randomly selected rural households were interviewed. Data collected from the questionnaires, were analyzed using the statistical analysis methods in SPSS, and Fitness model search EQS software. According to the results of Pearson's correlation tests, the findings of present study showed a significant and strong correlation between implementation of rural guide plan and the mental facet of life quality by a 0.75 correlation coefficient, so that rural guide plan explained 57% of the variation of dependent variable, and among guide plan dimensions the changing environmental rural affected the objective improvement of life quality of villagers by 29 percent. There is a direct and complete correlation in spatial distribution of relationship between the implementation of guide plan and the objective quality of life in 8 study villages.